Branding Tari Sedulang Setudung Untuk Generasi Muda Di Sumatera Selatan - Suci Ramadani Suci; Mukhsin Patriansah; Aji Windu Viatra (Penerbit dan Percetakan, CV. Picmotiv, 2024)
One of the typical Banyuasin traditional dances is the Sedulang Setudung Dance, which is usually performed to welcome guests. The main problem faced is how to regenerate the interest of the younger generation in loving and appreciating local arts, one of which is the Sedulang Setudung dance. In overcoming this problem, the author uses the design thinking method for data collection and data analysis through the 5W+1H method (what, why, who, where, why, how), thereby producing an idea that can be applied at the design stage as a problem solving plan that faced. The main aim of this design is to create a branding design for the Sedulang Setudung dance so that it will be popular again with the younger generation. The designs created produce works that are categorized into three media, namely issue media including posters, x-banners, main media in the form of promotional videos, and supporting media including t-shirts, tote bags, stickers, hats, pencil pouches, key chains. and tumblers. The application of this media uses illustrations of dancers, rampai talang batik and other supporting elements. It is hoped that this design can embrace the younger generation. Through this design, it is hoped that it will be able to contribute to introducing and preserving the sedulang setudung dance to the younger generation in South Sumatra.